Steelband in the Education System - Sullivan, Nestor; Belgrave, Ian "Teddy" (Express)
This is the third and final part in the three-part series on the steelband by Nestor Sullivan and Ian Belgrave. This article focuses on the foundation of the steelband movement internationally and the steelband programme in the school systems in many parts of the USA, Canada, the UK, Europe and Japan.
Keywords: Steel drum (Musical instrument); Steel band music; Music -- Instruction and study; Steel bands (Music) -- Education